Efficient and industrial production of H2SO4 from sulfur sludge by acidophilic cells in a membrane bioreactor via optimizing process. (20th March 2020) - Yang, Yiran; Qian, Can; Shi, Xingfu; Tian, Bingyan; Chu, Huichao; Wang, Jia; Xin, Baoping
Abstract: A large amount of sulfur-bearing hazardous wastes, including sulfur sludge, are generated in the production and processing of oil/natural gas/coal gas/biomass gas, which are difficult to dispose of with traditional processes, such as incineration or landfills. In the present work, a homemade membrane bioreactor (MBR) with an efficient volume of 10 m 3 was utilized to continuously and efficiently remove sulfur (S 0 ) from sulfur sludge and produce sulfuric acid (H2 SO4 ) by using chemoautotrophic acidophilic cells on an industrial scale for the first time. The bio-oxidation process was also modelled and optimized by using response surface methodology. The quadratic models describe the causal relationships between the production rate of H2 SO4 at pH 1.0 or the time required for the pH to decrease to 1.0 and three important control parameters (temperature, aeration rate and stirring velocity). The MBR maintained high-density growth of cells (≈2.1 × 10 9 /mL) throughout the entire operational period due to the excellent interception performance, establishing a basis for efficient sulfur removal and H2 SO4 production. Under the optimized process controls of 33.6 °C for the temperature, 3.1 m 3 /min for the aeration rate and 83 rpm for the stirring velocity, a high production efficiency of H2 SO4 at pH 1.0 (≈850 L/h) is obtained. Accordingly, the sulfur removal efficiency and sulfur residual concentrations reached 93% and 4.1% after 20 days of contact, respectively. The current study demonstrates that the MBR is suitable for industrial scale operations, for continuous and efficient sulfur removal and for production of H2 SO4 from sulfur-bearing hazardous wastes. The green microbial means not only save very expensive disposal expense of sulfur-bearing hazardous wastes but also gain benefits through the manufacture of valuable H2 SO4, displaying great business value and wide application prospect. Graphical abstract: Image 1 Highlights: Membrane bioreactor keeps much high density of acidophilic cells for efficient oxidation of S 0 . A maximum H2 SO4 production of ≈850 L/h with pH 1.0 is obtained under optimizing conditions. The sulfur removal efficiency in sulfur sludge reaches 93% after 20 days due to oxidation of S 0 . The sulfur residual content in sulfur sludge drops to 4.1% after 20 days due to sulfur removal. Membrane bioreactor is qualified for sulfur removal and production of H2 SO4 from sulfur sludge.